Development of a contextualized and policy-driven mentoring model for aspiring principals in public schools - Paranis, Maria Laarni Carla C.; Buenviaje, Jerome T.; Javiniar, Joel C.; Patriarca, Marian Christine V.; Vinluan, Lorelei R.; Manzano, Virgilio U. (Quezon City College of Education University of the Philippines Diliman, 2020)
This study was conducted to develop a mentoring model specifically designed for the aspiring principals in public schools. It explored the stories of the participants consisting of educational leaders, school heads and aspiring principals in public schools through a case study. The findings revealed that the participants defined mentoring as a helping relationship where both mentor and mentoree reflect and learn in the process that facilitates personal and professional development. It also revealed that mentoring fosters reflective interaction and supports professional development of aspiring principals where mentor and mentoree create and act on a leadership role. In this study, mentoring strategies such as sharing and discussion, empowering, shadowing and reflecting were employed to develop aspiring principals. Furthermore, mentoring conditions such as policy, time, human resources should be considered to ensure alignment of supportive mentoring environment. These findings led to the development of contextualized and policy-driven model for mentoring aspiring principals. This model may be used as a guide in the implementation of mentoring program for effective school leadership in the Philippine public schools.

Keywords: mentoring, school management, school leadership, school administration
Dissertation
Includes bibliographic references
Keywords: Educational leadership -- Philippines -- National Capital Region; Public schools -- Philippines -- National Capital Region -- Administration